PENGARUH INTEGRITAS TERHADAP PRODUKTIVITAS KERJA PEGAWAI - rifuandra sudirman; syamsir syamsir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This research is motivated by an indication that the lack of honesty, commitment and consistency in civil servants in carrying out their duties and obligations as well as low productivity in completing work. This study aims to determine 1) The effect of honesty on the work productivity of Civil Servants, 2) The effect of commitment to the work productivity of Civil Servants, 3) The Consistent Effect on Work Productivity for Civil Servants, and 4) The Influence of Integrity on the Civil Servants' work productivity . This research uses associative quantitative methods. The population of this study amounted to 72 people consisting of Civil Servants at the District Office and Lurah Office in the District of North Padang, and the sample of this study amounted to 70 respondents determined based on the Slovin formula with a significant level of 0.5%. The sampling of this research used the Multistage Random Sampling technique. This research instrument was questionnaire using a Likert scale measurement. The analysis of this study uses multiple linear regression test. The results of this study indicate that the honesty sub-variable significantly influences the work productivity of Civil Servants in Padang Utara District with the results of the regression test of the Adjusted R Square value of 0.230, the commitment sub-variable significantly influences the work productivity of the Civil Servants with the results of the Adjusted R Square value test of 0.225, the consistent sub-variable has a significant effect on the work productivity of Civil Servants with the regression test value of the Adjust R Square value of 0.348. Together the honesty, commitment and consistent sub-variables significantly influence the work productivity of Civil Servants in Padang Utara District with the result of a regression test of Adjusted R Square value of 0.373.